Avaliação de genes candidatos a variações do tamanho mésio-distal e vestíbulo-lingual de dentes permanentes - Gerber, Jennifer Tsi (2020)
The objective of this study was to evaluate the association of genetic polymorphisms in RUNX2, BMP4, BMP2, TGFβ1, EGF, SMAD6, ESR1, ESR2 and PTH with permanent tooth size (TS) variations. This cross-sectional study was carried out with 110 individuals of both sexes. Dental casts were used to measure the maximum crown dimensions of all fully erupted permanent teeth (except third molars) in the mesiodistal (MD) and buccolingual (BL) width. The DNA was obtained from the epithelial cells of the oral mucosa and the genetic polymorphisms of RUNX2 (rs59983488 and rs1200425), BMP4 (rs17563), BMP2 (rs235768 and rs1005464), TGFβ1 (rs1800470), EGF (rs4444903), SMAD6 (rs2119261 and rs3934908), ESR1 (rs2234693 and rs9340799), ESR2 (rs1256049 and rs4986938), and PTH (rs694, rs307247 and rs6256) were genotyped by real-time PCR. The data were submitted to statistical analysis with a significance level of 0.05. The genetic polymorphisms rs59983488, rs1200425, rs17563, rs235768, rs1005464, rs1800470, rs4444903, rs2234693, rs9340799, rs1256049 and rs4986938, rs694, rs307247 were associated with MD and BL TS in the maxillary and mandibular arch (p < 0.05). The polymorphism rs2119261 was associated with variation in TS only in the upper teeth (p < 0.05). In rs6256, there was an association only in the BL width of the upper left canine (p < 0.05). The rs3934908 was not associated with any TS (p > 0.05). Finally, this study showed that there is an association between variation in TS with genetic polymorphisms in RUNX2, EGF, TGFβ1, BMP2, BMP4, SMAD6, PTH, ESR1, and ESR2 indicating a possible role of these genes in tooth development.